Rizomas: espaços-tempos concretos e virtuais na literatura e na computação - Pedro de Freitas Veneroso (2016)
The aim of this research is to analyze the possible relationships between the literary universe and the computational environments, considering that both might configure virtual spaces where hypertextual and rhizomatic practices and techniques are developed in relation to theprocesses of reading and writing. Through historical and analytical forays, codes will be studied in relation to their interfaces with technologies, in a kind of cognitive archaeology of the literaryuniverse, of digital technologies and their present and past languages, in order to describe their influences on how humans experience the world. A philosophical inquiry based on the study ofthe hypertext and its intersections with Deleuze and Guattari's theory of the rhizome complements and expands the archaeological endeavor, functioning as conceptual frameworks to discuss issues and solutions related to computational and literary virtual environments, theircodes and modes of experience. The space-time common to hypertexts and rhizomes virtual places characterized by the perennial occurrence of connections and disconnections between diferent semiotic products can be described by the concepts of heterotopia, in Michel Foucault, and ucronism, in Edmond Couchot. Finally, literary explorations will precede some chapters, contextualizing and applying theoretical abstractions that permeate this work by describing situations where computational and literary virtual spaces clash with the concrete world, through presentations that demonstrate the social, cultural and cognitive ramifications of types of rhizomatic navigations in heterotopical and ucronical space-times.